The Practicality of STEAM Based Augmented Reality (AR) Learning Media for Vocational High School Students in Robotic System Subject - Dio Alvendri; Risfendra Risfendra; Resmi Darni; Rizky Ema Wulansari (Postgraduate, University of Mataram, 2024)
This study aims to create and implement STEAM-based Augmented Reality (AR) learning media for the class XI robotics systems curriculum at SMK N 1 West Sumatra. The research follows a Research and Development (R&D) approach using the ADDIE development model. Participants included class XI students and robotics systems teachers. Data collection methods comprised questionnaires and interviews, with descriptive data analysis employed to assess the validity and practicality of the developed learning media. The findings indicate that the STEAM-based AR learning media is effective. According to media expert validation, the average score was 0.88 (≥ 0.66), categorizing it as valid. Material expert validation yielded an average score of 0.85 (≥ 0.66), also marking it as valid. The practicality assessment showed that teacher responses averaged 90.14%, and student responses averaged 92.03%, both rated as very practical. Consequently, the STEAM-based AR learning media is considered suitable for class XI robotics systems at SMK N 1 West Sumatra, based on the validity and practicality tests